Political Connections, Women Commissioners, and Banking Performance: Evidence from Indonesia - Putriani, Tina; Nurmayanti M, Poppy; Mela, Nanda Fito; Basri, Yesi Mutia; Setiawan, Doddy; Kurnia, Pipin (Universitas Syiah Kuala, 2023)
Objective The purpose of this study is to investigate the effect of political connections on banking performance with women commissioners as a moderating variable.Design/Methodology The population of this study derive from banking sector listed on Indonesia Stock Exchange from 2016 to 2021 with the final sample of as many as 42 banks with a total of 252 observations. Hypothesis testing was performed using multivariate regression analysis.Results This study finds that commissioners who have political connections tend to report higher banking performance, as measured by ROA. Meanwhile, women commissioners tend to report lower banking performance (ROA). Furthermore, there is a positive influence from political connections to banking performance when there are women commissioners. In addition, this study employs alternative measures of banking performance, namely ROE and including bank risk. This study also replaces the measurement of political connections from dummy variables to a number of political commissioner members compared to total commissioners. In particular, these results are robust after replacing the measurement of political connections, the commissioners who have political connection will report higher banking performance than commissioners who have no political connections. However, political connection and women commissioners have no significant effect on banking performance, when using ROE as banking performance. Meanwhile, political connection has a negative impact on bank risk. It suggests that political connections can reduce bank risk by decreasing overdue credit (Non-Performance Loan).Research limitations/implications This study focuses primarily on the linear relationship with required gender diversity between political ties and banking performance. This study adds to the growing body of research on how political connection and gender affect banking performance.Novelty/Originality Gender diversity or women commissioners are still rare as the impact of commissioners' political connection on banking performance in Indonesia.